Development of an efficient remediation system with a low cost after identification of water pollutants including phenolic compounds in a tannery built-up area in Bangladesh. (October 2021) - Yuan, Tian; Tazaki, Akira; Hashimoto, Kazunori; Al Hossain, M.M. Aeorangajeb; Kurniasari, Fitri; Ohgami, Nobutaka; Aoki, Masayo; Ahsan, Nazmul; Akhand, Anwarul Azim; Kato, Masashi
Abstract: Water pollution caused by tannery wastewater is an important issue in developing countries. Most studies have focused on inorganic chemicals represented by chromium as a tannery-related main pollutant. This is the first study in which pollution of water by tannery-related organic chemicals was assessed by a combination of qualitative and quantitative analyses. Our quantitative analysis showed that the maximum concentration of total phenolic compounds (phenols), consisting of phenol, bisphenol F, p-cresol and chlorocresol, in canal water in a tannery built-up area in Bangladesh was >67-fold higher than the Environmental, Health and Safety (EHS) guideline value. Mapping of our results indicated tanneries as the sources of phenols pollution. Our original depurative, a hydrotalcite-like compound consisting of magnesium and iron (MF-HT), could adsorb all kinds of phenols and exhibited the highest phenol adsorption ability (115.8 mg/g) among reported hydrotalcite-like compounds. The levels of phenols in canal water samples were reduced to levels below the guideline value by using MF-HT with assistance of a photocatalytic reaction. Moreover, the mean level of chromium (112.2 mg/L) in canal water samples was decreased by 99.7% by using the depurative. Thus, the depurative has the potential for solving the problem of tannery-related water pollution by phenols and chromium. Graphical abstract: Image 1 Highlights: No data from qualitative and quantitative analyses of tannery-related organic pollution. Phenol level in canal water that is 100-fold higher than the US-EPA guideline value. Higher phenol removal ability (116 mg/g) of our original adsorbent of MF-HT in theory. An MF-HT adsorbent with highest ability to remove Cr, a main pollutant in tanneries. An effective adsorbent to remove both Cr and phenols from tannery wastewater.